The Position of Women in Islamic Family Law: A Study of Rights and Obligations in Marriage - Septiani, Rina (PT. Anagata Sembagi Education, 2025)
This research is motivated by the persistence of gender inequality in the understanding and practice of women's rights and obligations in marriage according to Islamic family law. One of the main problems is the assumption that women have a subordinate position in the household, which often stems from conservative interpretations of religious texts. This research aims to examine normatively and contextually the position of women in Islamic family law, as well as analyze the rights and obligations of women in marriage based on classical and contemporary fiqh perspectives. The method used is normative qualitative with a literature study approach to the verses of the Qur'an, hadith, and the opinions of scholars from various madhhabs. The results of the study show that in principle, Islam upholds equality and justice in the relationship between husband and wife, but in practice there is often a gap between legal norms and social reality, which is influenced by patriarchal culture and lack of contextual understanding. In conclusion, it is necessary to develop a more progressive and gender-just approach to Islamic family law so that women can play a role as autonomous and equal legal subjects in marriage.